This** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **) = 1 √ 2+ t 4 , and by FTC1, g ( x ) = F ( x 2 )-F (tan x ). Therefore, by chain rule, g ′ ( x ) = F ′ ( x 2 )2 x-F ′ (tan x ) sec 2 x = 2 x √ 2 + x 8-sec 2 x √ 2 + tan 4 x 3. Evaluate the integral ∫ π/ 4 1 1 + cos 2 θ cos 2 θ dθ. Solution: ∫ π/ 4 1 1 + cos 2 θ cos 2 θ dθ = ∫ π/ 4 1 ( 1 cos 2 θ + 1 ) dθ = ∫ π/ 4 1 ± sec 2 θ + 1 ² dθ = tan θ + θ ] π/ 4 1 = (1 + π/ 4)-(tan 1 + 1) = π/ 4-tan 1 . 2...

View
Full Document

- Fall '06
- McAdam
- Calculus, Derivative, Riemann integral, Riemann sum, Riemann